Enhancement in conductivity of boron doped diamond films deposited by the methanol/acetone/B2O3 system. (November 2018) - Li, Fan; Gou, Li
Abstract: The gaseous boron sources such as trimethylboron and borane have been wildly used for boron-doping of diamond film with a high conductivity. Methanol and acetone/B2 O3 /CH4 (C-B with CH4 ) has also been selected as a doping system for its low cost. But the resulting boron-doped diamond (BDD) film exhibited a lower conductivity. The BDD film was deposited by the system of methanol and acetone/B2 O3 without CH4 (C-B) and exhibited a higher conductivity and larger carrier concentration. It is found that oxygen plays an important role during the deposition. A large number of vacancies for boron filling can be generated in the diamond film from the CO bonds. The addition of CH4 decreased the number of oxygen atoms so that fewer vacancies occurred. Enhancement in conductivity results from more boron atoms in the diamond film using the mixed methanol/acetone/B2 O3 system. Highlights: Methanol and acetone/B2 O3 /CH4 has also been selected as a doping system for its low cost. The diamond film with a higher conductivity and carrier concentration was prepared by CH4 –free doping system. Many boron atoms occupied carbon vacancies which introduced by CO bonds and the following hydrogen etching. Oxygen atoms improved conductivity of boron doped diamond film based on a cheap doping system.